Nitrogen and Phosphorus Recovery From Anaerobically Pretreated Agro-Food Wastes: A Review - Campos, José Luis; Crutchik, Dafne; Franchi, Óscar; Pavissich, Juan Pablo; Belmonte, Marisol; Pedrouso, Alba; Mosquera-Corral, Anuska; Val del Río, Ángeles (Frontiers in Sustainable Food Systems, 2019)
Anaerobic digestion (AD) is commonly used for the stabilization of agro-food wastes and recovery of energy as methane. Since AD removes organic matter but not nutrients (N and P), additional processes to remove them are usually applied to meet the stringent effluent criteria. However, in the past years, there was a shift from the removal to the recovery of nutrients as a result of increasing concerns regarding limited natural resources and the importance given to the sustainable treatment technologies. Recovering N and P from anaerobically pretreated agro-food wastes as easily transportable and marketable products has gained increasing importance to meet both regulatory requirements and increase revenue. For this reason, this review paper gives a critical comparison of the available and emerging technologies for N and P recovery from AD residues.